1992
DOI: 10.1111/j.1745-6584.1992.tb01557.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Waste‐Water Irrigation on Aqueous Geochemistry Near Paris, Texas

Abstract: A comprehensive assessment of the environmental impact of a full‐scale, operating overland flow (OLF) land treatment system was made at the Campbell Soup (Texas), Inc. facility in Paris, Texas. The system treats over 16,000 m3/d of waste water and has been in operation for over 25 years. Field samples of soil, waste water, OLF runoff, and ground water collected during the study and detailed long‐term process records maintained by Campbell Soup were used as part of the evaluation. Geochemical data indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Salt precipitation occurs related to irrigation water evaporation, and precipitated salts can subsequently be leached by later irrigation or precipitation (Law 1987;Tedaldi and Loehr 1992). Practically, higher evapotranspiration rate in cultivated areas caused to more enrichment of dissolved ions and precipitating salts in these parts of the study area.…”
Section: Irrigationmentioning
confidence: 99%
“…Salt precipitation occurs related to irrigation water evaporation, and precipitated salts can subsequently be leached by later irrigation or precipitation (Law 1987;Tedaldi and Loehr 1992). Practically, higher evapotranspiration rate in cultivated areas caused to more enrichment of dissolved ions and precipitating salts in these parts of the study area.…”
Section: Irrigationmentioning
confidence: 99%
“…Its addition to some extent may occur due to cation exchange but definitely not to such level. Such high K values (22 out of 110 samples with concentration of >30 mg/l), averaging 16 (pre-monsoon) to 23 mg/l (post-monsoon), may have manifested as a result of partial or deficient fixation in the soil (Tedaldi and Lohar 1992;Tyagi 2003) of potassium applied in the form of fertilizers.…”
Section: Discussionmentioning
confidence: 98%
“…Ion exchange is common when groundwater flows through a clay bearing aquifer. Calcium and Na are often involved in ion exchange (Tedaldi and Lohar 1992;Tyagi 2003), the former replacing the latter. This exchange results in Ca depletion and proportionate enrichment of Na in groundwater.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With appropriate techniques of sampling of soils and/or soil water (Boulding 1995;Wilson and others 1995) the migration may be controlled in a real context, where the characteristics must be known. Examples of this type of ®eld study on leaching of pesticides can be found in Beltran and others (1993) and Azevedo and others (1997); on the transport of nitrates in Jemison and Fox (1994), Jabro and others (1995), and Morell and others (1996); and studies on puri®cation of wastewater through vadose zone in Bustamante (1990), Tedaldi and Loehr (1992), Esteller and others (1994), and Shahalam and others (1998). In arid or semiarid countries it is becoming more and more common to use urban wastewater for irrigation, and this is not always subjected to even a primary puri®cation process prior to being used.…”
Section: Introductionmentioning
confidence: 99%